Persistent Vulvar Itch Unresponsive to Treatment: A Case of Vulvar Schistosomiasis Caused by Schistosoma mansoni and a Brief Review of Literature - Anthony Gyening-Yeboah; Solomon E. Quayson (Case Reports in Infectious Diseases)
Background. Vulvar schistosomiasis is a female genital schistosomiasis (FGS), which occurs because of the damage caused by the presence of schistosome ova within the vulva. FGS is mostly misdiagnosed as a sexually transmitted infection. There is no reported case of vulvar schistosomiasis from Schistosoma mansoni in an immunocompetent or immunocompromised person in Ghanaian medical literature; however, there is a reported case of S. haematobium in an immunocompromised person. This is the first case of vulvar schistosomiasis from S. mansoni infection in an immunocompromised person. This case report discusses the need to consider vulvar schistosomiasis in patients with itchiness of the vulva. Case Presentation. A sixty-nine-year-old married woman presents with a persistent vulvar itch that is unresponsive to treatment. A clinical diagnosis of vulvar lichen planus unresponsive to medical therapy was made. A histopathological diagnosis of vulvar schistosomiasis was, however, made. Ziehl–Neelsen stain revealed the ova of Schistosoma mansoni. Symptoms resolved on administration of oral praziquantel. Conclusion. Vulvar schistosomiasis must be considered in clinical history-taking and investigation of signs and symptoms related to itchiness of the vulva. Ziehl–Neelsen staining is a helpful histopathology armamentarium to determine the species of schistosome ova.